Pemanfaatan Media Aktual Lingkungan untuk Meningkatkan Kemampuan Menghitung Perkalian di MIN Yogyakarta II - Karimatul Hissoh (Jurnal Pendidikan Madrasah, 2020)
This research aims to improve the ability to calculate the multiplication of grade III-C students in MIN Yogyakarta II. This research uses class action research methods including planning, implementation, observation, and reflection activities. easy to understand mathematics. The right media choices can be a bridge to the difficulty of primary school students in understanding this lesson. learning activities should be able to provide students with a real experience. Students are actively conducting explorations, experiments, testing, discussions or other activities that emphasize students being active in learning by utilizing the surrounding environment. The results showed that Students can see and feel directly in observing, converting the form of multiplication into a form of division, solving everyday problems involving multiplication and converting the multiplication form into a form of division.